Empathy and structural injustice in the assessment of patient noncompliance. (30th December 2021) - Wilson, Yolonda
Abstract: Empathy is generally considered important because it is linked to prosocial helping behaviors. To the extent that humans are thought to be social creatures, empathy is regarded as an important component of our general well‐being. Meanwhile, empathy skeptics argue that empathy is not as important as its proponents believe. While there is philosophical debate about the appropriate place for empathy in moral judgment, empathy is a taken‐for‐granted, good‐making feature of moral deliberation in healthcare. In this paper I offer an account of empathy and a critique of its moral significance before thinking specifically about the role that empathy plays in medicine. Finally, I offer a hypothetical case to show that in order to fully appreciate the skeptical position, empathy's role in health justice should be understood in the context of structural injustice. Although I ultimately defend the importance of empathy in healthcare environments, I show that any conception of empathy in healthcare should take seriously reasons for skepticism about empathy, notably its susceptibility to bias against disfavored groups.